Healthy building phytoarchitecture requires essential criteria for sustainable phylloremediation of contaminated indoor air - Ganjar Samudro; Harida Samudro; Sarwoko Mangkoedihardjo (Institute of Advanced Engineering and Science, 2024)
Various ambient air contaminants can spread into the indoor building through air transport. With the additional generation of contaminants from indoor activities, indoor air quality (IAQ) has the potential to be polluted. Indoor air pollution incidents can occur anytime, which is difficult to predict. Therefore, it is necessary to take action to improve IAQ as early as possible and sustainably. The solution to sustainable remediation is using plants to apply phylloremediation, which functions as leaves and leaf-associated microbial communities to reduce air contaminants. This study aims to provide new practical yet essential criteria for the sustainable operation of phylloremediation. This review is based on the latest results of a literature-based study. An analysis of the fundamental processes of plant life forms the basis for obtaining these criteria. The study emphasizes key criteria for phylloremediation encompassing the selecting plants with high transpiration and leaf-microbe synergy, and conducting maintenance by spraying water on leaves. These measures optimize efficiency and sustain the process for indoor air pollutant reduction. The final result summarises the new criteria for sustainable phylloremediation to maintain plant life. These essential criteria can be used for conducting experiments in empirical research, indoor design, and education for the community.